Linguistic Landscape as a Pedagogy of Reading for English Learning: A Case Study of Shop Names in Sidoarjo City - Nurul Uswatun Hasanah; Ahmad Munir; Slamet Setiawan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Learning English does not only occur in the four corners of the classroom, but is possible even within the immediate community of learners. Learning English can be improved through a variety of sources such as the linguistic landscape available. Based on Cenoz and Gorter, LL is particularly on major shopping streets and in commercial areas, which is sometimes the text has only one language, however often has two or more languages (2017). Mainly, in ths research is focused on LL in English language learning as pedagogical resource for young learners. In this case, focusing on senior high school level in Sidoarjo city’s who Javanese as a mother language is. The methodology of this research tha use mix method. Those are qualitative and quantitative method. For the result, the LL in the shop names that written in English is the highest language. Many shop names English language usage as the follows (34%) of the precentage. And the second grade that written in Indonesian languages (30%) score. However, there is no one shop names that written in Javanese. It will be giving a bilingual and trilingual language that used in the shop names written when Javanese language conducted of that. It is a good things that LL can be applied in English language material for learning. Based on the senior high school students’ in Sidoarjo area, there are highest desires can be imply LL in the material of the schools program?